Sistem Pendukung Keputusan Seleksi Beasiswa Ppa Dan Bbm Menggunakan Metode Fuzzy Ahp - Rekyan Regasari, Fauziah Mayasari Iskandar, Arief Andy Soebroto, (SMATIKA, 2013)
Each institute of education like university offered scholarships for students who have a good achievement and lack of financial. To assured that Academic Achievement Scholarship (PPA) and StudentLearning Assistance (BBM) delivered to the right person, we need a comprehensive system to make decisions. The selection process of PPA and BBM scholarships is a problem which recently discussed by students because there Â is Â a Â probability that Â the Â distribution is Â not Â well Â targeted,Â  the Â time Â is Â overdue, Â and Â the Â amountÂ  is inappropriate. We can use Fuzzy AHP method for this Decision Support System (DSS). AHP model can represent a Â problem into a hierarchy with levels: objectives, criteria, and alternatives and the fuzzy logic is used to minimize uncertainty value in AHP with crisp value. The analysis of software requirement system consists of actorâs identification and requirement list.Implementation of web-based system use HTML and PHP programming language that integrated with MySQL databases. The testing used are validation (Black Box) testing and accuracy testing. Black Box testing result is 100% which indicates that the functionality of the system fulfill the system requirements list. Accuracy testing result is 80% for PPA and 33.33% for BBM which indicate the DSS is running well with Fuzzy AHP method.